Engineered Elastomer Substrates for Guided Assembly of Complex 3D Mesostructures by Spatially Nonuniform Compressive Buckling. (2nd November 2016) - Nan, Kewang; Luan, Haiwen; Yan, Zheng; Ning, Xin; Wang, Yiqi; Wang, Ao; Wang, Juntong; Han, Mengdi; Chang, Matthew; Li, Kan; Zhang, Yutong; Huang, Wen; et al.
Abstract : Approaches capable of creating 3D mesostructures in advanced materials (device‐grade semiconductors, electroactive polymers, etc.) are of increasing interest in modern materials research. A versatile set of approaches exploits transformation of planar precursors into 3D architectures through the action of compressive forces associated with release of prestrain in a supporting elastomer substrate. Although a diverse set of 3D structures can be realized in nearly any class of material in this way, all previously reported demonstrations lack the ability to vary the degree of compression imparted to different regions of the 2D precursor, thus constraining the diversity of 3D geometries. This paper presents a set of ideas in materials and mechanics in which elastomeric substrates with engineered distributions of thickness yield desired strain distributions for targeted control over resultant 3D mesostructures geometries. This approach is compatible with a broad range of advanced functional materials from device‐grade semiconductors to commercially available thin films, over length scales from tens of micrometers to several millimeters. A wide range of 3D structures can be produced in this way, some of which have direct relevance to applications in tunable optics and stretchable electronics. Abstract : This work introduces approaches to assemble complex 3D mesostructures via compressive buckling induced by elastomer substrates with spatially engineered distributions of strain. Systematic studies using combined theoretical modeling and experiment illustrate the compatibility of the approach with advanced electronic materials and planar semiconductor technologies, and representative 3D structures with potential utility in tunable optics and stretchable electronics are highlighted.